Komunikasi Interversonal yang Efektif - Arfin Dalimunthe; Ella Sri Wahyu Ningsih; Suhairi Suhairi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2022)
Indonesia. The rise of these murder cases is due to the Indonesian nation experiencing a moral crisis. The crisis occurs because of the loss of a person's sense of empathy when communicating interpersonally with others. Someone who does not have empathy can potentially carry out aggressive acts that can harm themselves and others. Empathy is very important in communication because with empathy individuals are able to suppress aggressive actions and control emotions. Humans need to socialize with each other. In everyday life communication becomes an event to exchange information verbally and non-verbally. Empathy is also important in interpersonal communication, because interpersonal communication requires mutual understanding between the two communicating parties. This study focuses on exploring interpersonal communication skills in level (I) one students. The study was conducted on 5 students of level (I) one, because it is a transition stage from a student to a student. This study uses a qualitative approach with the type of phenomenological research, because the researcher wants to describe a meaning from the experiences of several individuals regarding the concept of communication skills. Based on the data obtained, it is known that level (I) one students have interpersonal communication skills but have not been able to apply them well in everyday life.